ANALISIS HUKUM TINDAK PIDANA PENGHINAAN SECARA ELEKTRONIK (Studi Kasus Putusan Nomor 2290 K/Pid.Sus/2015) - Fitriani Duha (Jurnal Panah Hukum, 2022)
The criminal act of defamation (insulting) is not infrequently carried out by a person or group of people through their social networks to express opinions without knowing that they are committing legal deviations, namely disturbing the rights of others. The purpose of this research is to find out how the Legal Analysis of Electronic Defamation Crime (Case Study: Decision Number 2290 K/Pid.Sus/2015)? . Research Methods the author uses a type of normative research. This type of normative legal research is legal research that examines literature studies, namely using secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. In this type of legal research, law is conceptualized as written in laws and regulations (law in books) or law is conceptualized as rules or norms which are standards for human behavior that are considered appropriate. Based on research findings and discussion that freedom of opinion is the right of every citizen and is also protected by the state as long as it does not conflict with Article 27 paragraph (3) of the Law on Information and Electronic Transactions (UU ITE). The offense of insult or defamation is not merely a general crime but a complaint offense. Complaint delict is an offense that can only be processed if it is complained by a person who feels aggrieved or has become a victim